Evaluation of measurement uncertainty of the results from dissolution test of letrozole tablets using combined approaches - Sonja Mandovski; Hrisanta Godzo; Jelena Acevska; Natalija Nakov; Jasmina Tonic-Ribarska; Katerina Brezovska (Makedonsko Farmacevtski Bilten, 2024)
This paper presents two simple combined approaches for estimating measurement uncertainty of dissolution tests of tablets containing 2.5 mg letrozole. The first approach integrates a top-down approach based on data from the validation study with the data from the qualification of the dissolution apparatus. The second top-down approach combines the data from participation in PTS with the uncertainty related to standard and sample solutions preparation. Additionally, a bottom-up approach for estimating the measurement uncertainty was applied to identify the variability sources and to evaluate their contributions to the combined standard uncertainty. The results indicate that the main contributor to the combined standard uncertainty is the standard uncertainty related to the dissolution apparatus (81.5%), followed by the method precision (8.7%). Both combined approaches (validation data with instrument qualification and PTS data with the uncertainty of testing solutions) resulted in similar measurement uncertainty estimates to those obtained with the bottom-up approach, suggesting that either approach can be effectively used for uncertainty estimation, depending on data availability.